Teresa Basile. Infancias. La narrativa argentina de HIJOS (2019). Buenos Aires: Eduvim, 2019, 297 pp. - Tavernini, Emiliano (Badebec, 2019)
Teresa Basile. Infancias. La narrativa argentina de HIJOS (2019). Buenos Aires: Eduvim, 2019, 297 pp.